2016
DOI: 10.1016/j.mito.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiolipin fatty acid remodeling regulates mitochondrial function by modifying the electron entry point in the respiratory chain

Abstract: Modifications of cardiolipin (CL) levels or compositions are associated with changes in mitochondrial function in a wide range of pathologies. We have made the discovery that acetaminophen remodels CL fatty acids composition from tetralinoleoyl to linoleoyltrioleoyl-CL, a remodeling that is associated with decreased mitochondrial respiration. Our data show that CL remodeling causes a shift in electron entry from complex II to the β-oxidation electron transfer flavoprotein quinone oxidoreductase (ETF/QOR) pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 48 publications
1
21
0
Order By: Relevance
“…It is essential for optimal activities of individual respiratory system complexes and supercomplexes, of ATP synthase and adenine nucleotide translocase (Paradies et al 1837). Cardiolipin content and remodeling changes the overall efficiency of the respiratory system (Vergeade et al 2016;Ye et al 2016). In our study, we observed alterations in cardiac cardiolipin fatty-acid species composition, namely a loss of the symmetric tetralinoleoyl-CL in favor of more asymmetric cardiolipins with shorter and more saturated chains (Fig.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…It is essential for optimal activities of individual respiratory system complexes and supercomplexes, of ATP synthase and adenine nucleotide translocase (Paradies et al 1837). Cardiolipin content and remodeling changes the overall efficiency of the respiratory system (Vergeade et al 2016;Ye et al 2016). In our study, we observed alterations in cardiac cardiolipin fatty-acid species composition, namely a loss of the symmetric tetralinoleoyl-CL in favor of more asymmetric cardiolipins with shorter and more saturated chains (Fig.…”
Section: Discussionmentioning
confidence: 50%
“…Cardiolipin content and remodeling changes the overall efficiency of the respiratory system (Vergeade et al. 2016; Ye et al. 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This “conical” shaped and double negatively charged CL is asymmetrically distributed in the IMM with a higher concentration of CL on the inner side of the IMM. The respiratory complexes and the adenine nucleotide carrier have an absolute requirement for CL and these complexes constitute much of the IMM protein [83-86]. With a high protein/lipid ratio ~3:1 in the IMM [87] and with CL being about ~20% of the (cardiac) mitochondrial phospholipids, the weight ratio of protein/CL phospholipids is ~15:1.…”
Section: Cardiolipin Its Molecular Structure Homo- and Hetero-acylamentioning
confidence: 99%
“…[4][5][6][7] Modifying the packing of the lipid can lead to structural changes and instabilities in the shape of the membrane. [1,8,9] By means of controlled environmental alterations, these changes can be investigated.…”
Section: Introductionmentioning
confidence: 99%